Reconstruction of the East Africa and Antarctica continental margins - Nguyen, Luan C.; Hall, Stuart A.; Bird, Dale E.; Ball, Philip J. (Journal of geophysical research. Solid earth, 2016)
The Early Jurassic separation of Antarctica from Africa plays an important role in our understanding of the dispersal of Gondwana and Pangea. Previous reconstruction models contain overlaps and gaps in the restored margins that reflect difficulties in accurately delineating the continent‐ocean‐boundary (COB) and determining the amount and distribution of extended continental crust. This study focuses on the evolution of the African margin adjacent to the Mozambique Basin and the conjugate Antarctic margin near the Riiser‐Larsen Sea. Satellite‐derived gravity data have been used to trace the orientations and landward limits of fracture zones. A 3‐D gravity inversion has produced a crustal thickness model that reliably quantifies the extent and amount of stretched crust. Crustal thicknesses together with fracture zone terminations reveal COBs that are significantly closer to the African and Antarctic coasts than previously recognized. Correlation of fracture zone azimuths and identified COBs suggests Antarctica began drifting away from Africa at approximately 171 Ma in a roughly SSE direction. An areal‐balancing method has been used to restore the crust to a uniform prerift thickness so as to perform a nonrigid reconstruction for both nonvolcanic and volcanic margins. Both margins reveal a trend of increasing extension from east to west. Our results suggest Africa underwent extension of 60–120 km, while Antarctic crust was stretched by 105–180 km. Various models tested to determine the direction of extension during rifting suggest that Antarctica moved away from Africa in a WNW‐ESE direction during the period between 184 and 171 Ma prior to the onset of seafloor spreading. Key Points Early Jurassic rifting between Africa and Antarctica took place in a WNW‐ESE direction Eastern part of the Mozambique Coastal Plain is underlain by oceanic crust